2019
DOI: 10.1111/ecca.12322
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Social Value and Returns to Long Hours

Abstract: This paper examines the phenomenon of uncompensated long hours in jobs with pro‐social characteristics and presents evidence that long‐hour wage premiums and occupational social value are substitutes in compensating salaried workers who supply hours exceeding the standard working week. I show that the social value of an occupation—in particular the degree to which jobs involve helping or providing service to others—is inversely related to long‐hour pay. Allowing for heterogeneity in the degree to which workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The elasticities tend to increase over time but are always lowest for teachers. 6 Occupations in the health care sector and in community and social service also have low elasticity of earnings with respect to hours; Gicheva (2020b) showed that earnings in occupations with high pro-social value tend to change relatively little with hours as workers in these occupations are more likely to donate labor.…”
Section: Elasticity Of Teachers’ Earnings With Respect To Hoursmentioning
confidence: 99%
“…The elasticities tend to increase over time but are always lowest for teachers. 6 Occupations in the health care sector and in community and social service also have low elasticity of earnings with respect to hours; Gicheva (2020b) showed that earnings in occupations with high pro-social value tend to change relatively little with hours as workers in these occupations are more likely to donate labor.…”
Section: Elasticity Of Teachers’ Earnings With Respect To Hoursmentioning
confidence: 99%
“…A large literature on the part-time wage penalty focuses on the increasing profile below 40 hours. Some work examines wages associated with long hours, including, for example,Hirsch (2005),Kuhn and Lozano (2008),Michelacci and Pijoan-Mas (2012),Goldin (2014),Weeden et al (2016),Yurdagul (2017),Gicheva (2020),Denning et al (2019),Fuentes and Leamer (2019) andShao et al (2021).…”
mentioning
confidence: 99%
“…The more recent research on compensating differentials and job meaning, dominated by case studies and experiments, does not focus on the classic distinction between high- and low-education workers that dominates the survey-based job values research. But recent studies still offer reason to expect higher-educated workers are particularly responsive to the prosocial job amenity: negative pay tradeoffs are identified for elite college graduates (Frank 2010), salaried workers (Gicheva 2020), lawyers (Carnahan, Kryscynski, and Olson 2017), and consultants (Bode, Singh, and Rogan 2015). These consistent findings across different types of highly educated, salaried, and professional workers provide warrant to expect such workers will respond to a prosocial job amenity.…”
Section: Inequality-reducing Prosocial Wage Effectsmentioning
confidence: 99%